Effectiveness of Hydrochloric Acid Activated Bentonite in Local Salt Purification - Muslimah Muslimah; Puji Wahyuningsih; Yusnawati Yusnawati (Elkawnie: Journal of Islamic Science and Technology, 2023)
Abstract: Various purification techniques have been developed to improve the quality of local salt, especially the NaCl content of more than 94%. One of the binding materials used in salt purification is bentonite. This study aims to synthesize modified bentonite using hydrochloric acid (HCl) solution and measure the metal content of NaCl, Pb, Ca, and Mg using AAS. The synthesis of activated bentonite was carried out using the hydrolysis method using 0.1 M HCl (1:10). Bentonite was separated from the filtrate and dried at 110°C for 2 hours. Bentonite, which had been activated with HCl, was dried again at 170°C for four hours. Analytical methods such as XRD, FTIR, and SEM were used to characterize HCl-activated bentonite. The results of the analysis showed that the acid activation process did not change the basal spacing d001 on the bentonite diffractogram. FTIR analysis showed that there was a shift in the -OH stretching vibration towards a lower wave number and a decrease in the absorption intensity. The activation process will reduce the pore size and increase the surface area and porosity of the bentonite. The results of the AAS analysis showed that the NaCl content in the salt increased after the purification process using acid-activated bentonite, followed by a decrease in the metal content of Mg. Based on the results of the analysis, it can be concluded that HCl-activated bentonite is effectively used in the salt purification process to improve salt quality.Abstrak:Berbagai teknik pemurnian telah dikembangkan untuk meningkatkan kualitas garam lokal, khususnya kandungan NaCl besar dari 94%. Salah satu zat pengikat yang digunakan dalam pemurnian garam adalah bentonit. Penelitian ini bertujuan untuk mensintesis bentonit termodifikasi menggunakan larutan asam klorida (HCl), dan mengukur kadar logam NaCl, Pb, Ca, dan Mg menggunakan metode SSA. Sintesis bentonit teraktivasi dilakukan menggunakan metode hidrolisis menggunakan  0,1 M HCl (1:10).Bentonit dipisahkan dari filtrat dan dikeringkan pada suhu 110°C selama 2 jam. Bentonit yang telah diaktivasi dengan HCl dikeringkan kembali pada suhu 170°C selama empat jam. Metode analisis seperti XRD, FTIR, dan SEM digunakan untuk mengkarakterisasi bentonit teraktivasi HCl. Hasil analisis menunjukkan bahwa proses aktivasi asam tidak mengubah basal spacing d001 pada difraktogram bentonit. Analisis FTIR menunjukkan terjadi pergeseran vibrasi ulur -OH ke arah bilangan gelombang yang lebih rendah dan penurunan intensitas serapan. Proses aktivasi akan memperkecil ukuran pori dan memperbesar luas permukaan serta porositas pada bentonit. Hasil analisis SSA menunjukkan bahwa kandungan NaCl pada garam mengalami peningkatan setelah proses pemurnian menggunakan bentonit teraktivasi asam yang diikuti dengan penurunan kadar logam Mg. Berdasarkan hasil analisis dapat disimpulkan bahwa bentonit teraktivasi HCl efektif digunakan dalam proses pemurnian garam untuk meningkatkan kualitas garam.